Complexification methods of interval forecast estimates in the problems on shortterm prediction - Romanenkov, Yuri; Danova, Mariia; Kashcheyeva, Valentyna; Bugaienko, Oleg; Volk, Maksym; Karminska-Bielobrova, Maryna; Lobach, Olena (Eastern-European Journal of Enterprise Technologies, 2018)
We solved the problem of improvement of methodological base for a decision support system in the process of short-term prediction of indicators of organizational-technical systems by developing new, and adapting existing, methods of complexification that are capable of taking into consideration the interval uncertainty of expert forecast estimates. The relevance of this problem stems from the need to take into consideration the uncertainty of primary information, predetermined by the manifestation of NON-factors. Analysis of the prerequisites and characteristics of formalization of uncertainty of primary data in the interval form was performed, the merits of interval analysis for solving the problems of complexification of interval forecast estimates were identified. Brief information about the basic mathematical apparatus was given: interval arithmetic and interval analysis. The methods of complexification of forecast estimates were improved through the synthesis of interval extensions, obtained in accordance with the paradigm of an interval analysis. We found in the course of the study that the introduction of the analytical preference function made it possible to synthesize the model of complexification in a general way, by aggregating the classes of hybrid and selective models in a single form for the generation of consolidated predictions based on interval forecast estimates. This allows obtaining complexification predictions based on the interval forecast estimates, thereby ensuring accuracy of the consolidated short-term prediction. Critical analysis of the proposed methods was performed and recommendations on their practical application were developed. Recommendations for parametric setting of the analytic function of preferences were stated. Using the example, the adaptive properties of the interval model of complexification were shown.